Developing a methodology to investigate the correlation between seafarer students' perception of authenticity in assessment and their achievement. Issue 3 (2nd July 2020) - Ghosh, Samrat; Bowles, Marcus; Abeysiriwardhane, Apsara
ABSTRACT: Past research shows seafarer students perceive traditional assessment methods used in maritime education and training (MET) institutes as disengaging, making them adopt surface-learning approaches towards acquiring essential knowledge and skills required for the workplace. Instead of developing skills that may be transferred to shipboard tasks, disengaged seafarer students focus only on achieving the minimum score required to attain a 'pass' grade for their certification. In this paper, a quantitative research methodology is developed to investigate seafarer students' perception of authenticity to workplace tasks in decontextualised traditional assessments versus authentic assessments conducted in real world contexts. The methodology will further correlate the perceptions to student achievement (measured using assessment scores) in the assessment tasks. The paper describes the research design and identifies the ethical issues. Procedures to address validity and reliability of the research are also established. Future research aims to implement the methodology to conduct research in a selected educational institute and a unit of competence. However, this paper acknowledges that the methodology should be replicated in other educational institutes for different units of competence to compare and generalise findings.